Macroinvetebrate Assemblages as Indicators of Water Quality of the West Seti River, Bajhang, Nepal - Matangulu, Mohana; Gurung, Smriti; Prajapati, Meera; Jyakhwo, Rabindra (International Journal of Environment, 2017)
Water quality of the West Seti River, a tributary of the Karnali in West Nepal was assessed using macroinvertebrates as bioindicators. The main objective of the study was to assess the ecological water quality of the West Seti River and to generate a baseline data on macroinvertebrate assemblages. The sampling was conducted during December 2015 and a total of 11 sampling sites were selected from the West Seti River and its tributaries. Qualitative samples of macroinvertebrates were collected from different habitats. Selected physico-chemical parameters such as pH and temperature were estimated on-site. Dissolved oxygen (DO) was estimated by Winkler’s method. The macroinvertebrate samples were enumerated and identified up to Family level following standard literature. Chi-square test was performed to see whether macroinvertebrate taxa varied significantly along the altitudinal gradient and between the West Seti River and its tributaries. An ecological assessment tool Nepalese Biotic Score/ Average Score Per Taxon (NEPBIOS/ASPT) was applied to assess the water quality of the sampling sites. The pH value ranged from 7.9 to 8.7 indicating the alkaline nature of the river. A total of 1666 individuals belonging to 34 Families and 7 Orders of macro-invertebrates were observed. The highest diversity of the macroinvertebrate taxa was observed at site T5 with nineteen Families whereas the lowest taxa diversity was observed at R3 with only five Families. The variation in macroinvertebrate assemblages between the sub-tropical and temperate zones; and the West Seti River and its tributaries were not significant. NEPBIOS/ASPT revealed a score of Water Quality Class of III-IV at Site R3 indicating that the site was polluted. This site was characterized by the abundance of red Chironomids which are considered as the indicators of organic pollution. International Journal of Environment Volume-6, Issue-3, Jun-Aug 2017, page: 25-45